Bloom of Peridinium quinquecorne abé in la Ensenada de la Paz, Gulf of California (july 2003) - Gárate-lzárraga, Ismael; Muñetón-Gómez, María del Socorro (Instituto de Ecología, A.C., 2008)
Microalgae blooms are frequent and periodic throughout the year in La Ensenada de La Paz, a lagoon formed by a large sand bar enclosed at the southern end of the Bahía de La Paz in the southwestern Gulf of California. Brown patches of the dinoflagellate Peridinium quinquecorne Abé, an armored dinoflagellate that is cosmopolitan in neritic and estuarine waters, were observed in July 2003 near a beach at the mouth of the lagoon. The patches were about 50-100 m long by 10-15 m wide and persisted for two days when water temperature was 26.2 to 27 °C. The blooms occurred after four days of a heavy rain. Abundance of P. quinquecorne varied from 3.4 to 6.4 × 106 cells l-1 and chlorophyll a varied from 13.20 to a continuous re-suspension of sediment caused by wave action. The higher nutrient content promoted formation of patches of P. quinquecorne in this part of the lagoon.